Emily Dickinson’s Line Breaks in Her Envelope Poems - Antoine Cazé (Transatlantica)
By taking a close look at the poems Emily Dickinson wrote, in the last fifteen years or so of her life, on envelopes (as gathered and transcribed in The Gorgeous Nothings, edited by Marta Werner and Jen Bervin), this article addresses the question of writing on a constrained surface—itself riddled with vertical, horizontal and oblique lines acting as so many “breaks.” How did Dickinson tackle the material space of inscription in (de)composing her poems? The often playful way in which she stages her line breaks indicates how aware she was of the relationship between her words and their various poetic “envelopes.” Here, the materiality of the medium becomes part of the meaning of the poems, and further contributes to the fluidity with which Dickinson positions her writing on the limits between the poetic and the epistolary.